Evaluating Tourism Export Performance in Uzbekistan: Evidence from Empirical Survey Findings - Bekmurodova F.A (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Tourism export has emerged as a strategic economic sector for diversifying national income, particularly for countries possessing substantial cultural and natural resources. Specific background: Uzbekistan, despite its rich cultural heritage and ongoing infrastructure development, faces challenges in maximizing its tourism export potential in the competitive global market. Knowledge gap: While previous studies have examined general tourism development patterns in Uzbekistan, empirical evidence regarding international visitors' perceptions and experiences remains notably limited. Aims: This study addresses this gap by investigating tourism export challenges from foreign visitors' perspectives through systematic survey analysis. Results: Based on questionnaire data from 172 international tourists collected during 2020-2023, findings reveal critical deficiencies in marketing strategies (84% rated performance as inadequate), limited infrastructure for eco-tourism and adventure tourism, and insufficient global information dissemination, though gastronomic and cultural tourism received favorable assessments. Novelty: This research contributes original empirical insights through direct visitor feedback rather than econometric modeling, providing authentic perspectives on service quality gaps. Implications: The study offers evidence-based recommendations for enhancing market segmentation, upgrading tourism facilities, and implementing targeted marketing interventions to strengthen Uzbekistan's competitive position in international tourism markets.Highlight : Highlights the underused tourism export potential despite strong cultural and historical assets. Shows low marketing visibility and limited eco-adventure facilities as major barriers. Emphasizes survey-based evidence revealing visitors’ needs for better infrastructure and diversified tourism products. Keywords : Tourism Export Performance, Visitor Perceptions, Service Quality, Marketing Gaps, Infrastructure Challenges